Show us the maze and we will help
Answer:
Proofs
Step-by-step explanation:
![f(x) = x + \frac{3}{2}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%20%2B%20%20%5Cfrac%7B3%7D%7B2%7D%20)
![y = x + \frac{3}{2}](https://tex.z-dn.net/?f=y%20%3D%20x%20%2B%20%20%5Cfrac%7B3%7D%7B2%7D%20)
![x = y + \frac{3}{2}](https://tex.z-dn.net/?f=x%20%3D%20y%20%2B%20%20%5Cfrac%7B3%7D%7B2%7D%20)
![x - \frac{3}{2} = y](https://tex.z-dn.net/?f=x%20-%20%20%5Cfrac%7B3%7D%7B2%7D%20%20%3D%20y)
![{f}^{ - 1} (x) = x - \frac{3}{2}](https://tex.z-dn.net/?f=%7Bf%7D%5E%7B%20-%201%7D%20%28x%29%20%3D%20x%20-%20%20%5Cfrac%7B3%7D%7B2%7D%20)
They are not inverse because f^-1(x) = x - 3/2 is not the inverse to g(x) = 2x - 3.
Answer:
Hopefully you can see the image.
Basically what's going on is the shape is being reflected over this line (x = -1) rather than the origin line.
Hope this helps :)
Answer:
-21/4
Step-by-step explanation: